Livelihood Strategies, Social Structures, and Household Dependence on NTFPs in Dadeldhura - Paneru, Tekraj (Journal of Advanced Academic Research, 2025)
This paper clarifies its unique contribution by examining how household socio-economic and demographic factors interact with ecological conditions to shape livelihood strategies, highlighting the overlooked role of non-timber forest products (NTFPs) in Dadeldhura district, Nepal. While NTFPs are often undervalued and insufficiently documented at the local level, this study demonstrates their significance as complements to subsistence agriculture and as coping mechanisms under ecological and demographic pressures. A cross-sectional quantitative research design was applied, surveying 222 households with structured questionnaires in multi-stage sampling to capture ecological and social diversity. Descriptive statistics and cross-tabulations were used to assess associations between NTFP use and household characteristics such as caste status and occupation, supplemented by secondary census and government data. Results indicate that eco-diversity, measured through climatic and soil variation, directly affects agricultural reliability, driving greater dependence on NTFPs in less productive areas. Demographic pressures (notably population growth and land fragmentation) further reinforce this reliance. Social hierarchy was also crucial: socially excluded groups (particularly Dalits) had stronger dependence on NTFPs, with women playing an active role in collection and processing. Overall, the study uniquely contributes by integrating ecological, demographic, and social dimensions to explain household livelihood strategies, offering insights into how marginalized groups sustain rural economies through NTFPs.